Thioesterase Domains of Fungal Nonreducing Polyketide Synthases Act as Decision Gates during Combinatorial Biosynthesis - Yuquan Xu; Tong Zhou; Shuwei Zhang; Li‐Jiang Xuan; Jixun Zhan; István Molnár (2013)
A crucial step during the programmed biosynthesis of fungal polyketide natural products is the release of the final polyketide intermediate from the iterative polyketide synthases (iPKSs), most frequently by a thioesterase (TE) domain. Realization of combinatorial biosynthesis with iPKSs requires TE domains that can accept altered polyketide intermediates generated by hybrid synthase enzymes and successfully release "unnatural products" with the desired structure. Achieving precise control over product release is of paramount importance with O-C bond-forming TE domains capable of macrocyclization, hydrolysis, transesterification, and pyrone formation that channel reactive, pluripotent polyketide intermediates to defined structural classes of bioactive secondary metabolites. By exploiting chimeric iPKS enzymes to offer substrates with controlled structural variety to two orthologous O-C bond-forming TE domains in situ, we show that these enzymes act as nonequivalent decision gates, determining context-dependent release mechanisms and overall product flux. Inappropriate choice of a TE could eradicate product formation in an otherwise highly productive chassis. Conversely, a judicious choice of a TE may allow the production of a desired hybrid metabolite. Finally, a serendipitous choice of a TE may reveal the unexpected productivity of some chassis. The ultimate decision gating role of TE domains influences the observable outcome of combinatorial domain swaps, emphasizing that the deduced programming rules are context dependent. These factors may complicate engineering the biosynthesis of a desired "unnatural product" but may also open additional avenues to create biosynthetic novelty based on fungal nonreduced polyketides.